Developing wine consumption behavior models by young Czech consumers. - Pacheco Carrillo, Gerardo; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis explores the changing environment of consumer behavior in Czech wine consumers. With research into motivators, key attributes and consumer traits that are currently driving trends in the wine industry and how this changes are having a strong effect not only in the wine industry but also in consumer behavior models overall.
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses